Composite material for monitoring leakage position of drilling fluid as well as preparation method and application of composite material
Through the acoustic logging technology of three-layer composite materials, the problem of difficulty in monitoring the location and depth of the drilling fluid leakage in the existing technology is solved, and a safe and efficient monitoring effect is achieved, avoiding damage to downhole tools and human bodies.
Patent Information
- Application Number
- CN202410009222.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-02
- Publication Date
- 2025-07-04
AI Technical Summary
The prior art is difficult to safely and effectively monitor the location and depth of drilling fluid leakage, and radioactive indicators are harmful to downhole tools and humans.
Three-layer composite materials, including high-density metal particles, elastic material coating and shell layer, are used to monitor the leakage position and depth through acoustic logging instruments, and use the characteristic acoustic characteristics of the composite materials for measurement.
It realizes safe and efficient monitoring of the location and depth of drilling fluid leakage, avoiding damage to downhole tools and human bodies.
Smart Images

Figure CN120243905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of petroleum engineering. Further, it relates to a composite material for monitoring the position of drilling fluid loss, a preparation method thereof, and an application thereof. Background Art
[0002] Well loss is a common downhole complex situation in drilling engineering, and most drilling processes have varying degrees of loss. Severe well loss can lead to a decrease in wellbore pressure, affect normal drilling, cause wellbore instability, induce formation fluid to flow into the wellbore and blowout, etc. The occurrence of well loss not only brings losses to the drilling project, but also causes great difficulties for the exploration and development of oil and gas resources. The lost circulation fluid used after the occurrence of loss will contaminate the reservoir, resulting in the logging curve being unable to reflect the true formation information, bringing great difficulties to the identification of formation fluid in the later stage. After well loss occurs, it is difficult to determine the location and depth of the loss.
[0003] At present, the methods for determining the well loss position include instrument measurement methods, such as the spiral flowmeter method, well temperature measurement method, resistivity measurement method, etc. However, due to the unknown fracture and cave morphology at the loss position, it is difficult to determine the depth of the lost drilling fluid.
[0004] Chinese Patent CN206987806U discloses a split-type drilling fluid loss position measuring instrument, including a drilling fluid loss position measuring instrument and a self-floating data reading device. Among them: the drilling fluid loss position measuring instrument mainly consists of a male joint assembly, a data storage cabin, an instrument circuit cabin, a battery cabin, a flow sensor, a temperature sensor, a pressure sensor, an outer cylinder short joint, and an insulating support rod. The male joint assembly is connected to a docking male needle. The self-floating data reading device includes an anti-collision head, a shock absorber, a floating cylinder assembly, and a female joint body. Among them, a storage and circuit cabin and a docking female needle are provided in the female joint body; the docking female needle is inserted and matched with the docking male needle. The measuring instrument part is installed in the form of a short joint near the bit, records and stores the loss parameters, and can read and analyze the data at any time by using the self-floating device, which has little impact on the drilling construction and is beneficial to reducing the well control risk.
[0005] Chinese Patent CN116066085A discloses a device and method for determining the position of drilling fluid leakage, which relates to the technical field of drilling detection, and particularly to a device and method for determining the position of drilling fluid leakage. The device for determining the position of drilling fluid leakage includes a drill collar and a testing mechanism. An induction chamber and a signal processing chamber are formed on the side wall of the drill collar. The induction chamber is provided with a flow hole communicating with the external annulus; the testing mechanism includes an induction component, a signal processing system and a signal line. The signal line connects the induction component and the signal processing system. The induction component is located in the induction chamber and is configured to obtain the parameters of the annulus drilling fluid. The signal processing system is located in the signal processing chamber and is configured to receive, process and store the signals obtained by the induction component. The above device for determining the position of drilling fluid leakage can directly measure the parameters of the annulus drilling fluid, with accurate and reliable data, and the determination method is simple to operate.
[0006] Chinese Patent CN109424356A discloses a system and method for detecting the position of drilling fluid leakage. The system includes: a plurality of tracers for measuring the state parameters of the drilling fluid at the position where they are located during movement; a plurality of measurement-while-drilling subsections for measuring the state parameters of the drilling fluid at the depth where they are located to obtain the reference depth and the corresponding reference state parameters of the drilling fluid; and a data processing device configured to obtain the drilling fluid state parameter curve of the well according to the drilling fluid state parameters collected by the plurality of tracers, and determine the depth of leakage according to the change of the drilling fluid state parameter curve, in combination with the reference depth and the reference state parameters of the drilling fluid transmitted by the plurality of measurement-while-drilling subsections. The provided system and method for detecting the position of drilling fluid leakage are accurate in measurement, simple in instrument operation, and convenient to lower. They can be used for measuring the position of drilling fluid leakage in high-temperature, high-pressure and drilling fluid environments.
[0007] Chinese Patent CN113687411A discloses a method for predicting the azimuth of in-situ stress based on microseismic, which includes the following steps: S1: obtaining the microseismic data and well trajectory data of the target well; S2: sampling the microseismic data according to the number of fracturing stages of the target well; S3: performing clustering analysis on the microseismic data of each fracturing stage to obtain the microseismic data of the artificial fractures in each fracturing stage; S4: respectively fitting the microseismic data of the artificial fractures in each fracturing stage to obtain the intercept and slope of the fitting curve of each fracturing stage; S5: calculating the arctangent value of the slope of each fracturing stage to obtain the angle of the artificial fractures in each fracturing stage, and the angle of the artificial fractures in each fracturing stage is the azimuth of the maximum horizontal principal stress in each fracturing stage. It can obtain the azimuth of the artificial fractures more accurately, so as to more accurately predict the horizontal stress azimuth of the formation and provide technical support for reservoir fracturing transformation.
[0008] Chinese Patent CN110847897A discloses a method for actively detecting well leakage using a radioactive indicator. The method includes the following steps: adding a predetermined content of radioactive indicator to the drilling fluid while drilling; sequentially arranging a first gamma value detection point and a second gamma value detection point at the near-bit end of the drill string in the direction opposite to the drilling direction; the first gamma value detection point and the second gamma value detection point respectively detect the gamma values of the radioactive indicator at different well depths in the formation to be detected, and determine whether there is well leakage at this well depth according to the change of the detection values of the first gamma value detection point and the second gamma value detection point at the same well depth; calculate the leakage position of the drilling fluid while drilling. It can actively detect the well leakage position, with a fast well leakage discovery speed and a short delay time.
[0009] Currently, there is a method for actively detecting well leakage using a radioactive indicator that can monitor the leakage position and depth. However, radioactive elements are harmful to downhole tools and the human body. Therefore, it is necessary to provide a new material and method for monitoring the leakage position of drilling fluid that are harmless to the human body and the environment. Summary of the Invention
[0010] To solve the problems existing in the prior art, the present invention provides a composite material for monitoring the leakage position of drilling fluid, its preparation method and application. The present invention can achieve safe and efficient measurement of the leakage position and depth through a sonic logging instrument.
[0011] One of the purposes of the present invention is to provide a composite material for crack monitoring.
[0012] The composite material for crack monitoring described in the present invention includes:
[0013] High-density metal particles, an elastic material coating coated on the high-density metal particles, and an outer shell layer coated on the elastic material;
[0014] The ratio of the radius of the high-density metal particles to the thickness of the elastic material coating is 1:(1 - 5);
[0015] The thickness of the outer shell layer is 50 - 500 microns.
[0016] Preferably,
[0017] The ratio of the radius of the high-density metal particles to the thickness of the elastic material coating is 1:(2 - 3);
[0018] The thickness of the outer shell layer is 50 - 100 microns.
[0019] Preferably,
[0020] The composite material is spherical particles. Preferably, the spherical particles are 10 mesh - 20 mesh, preferably 10 mesh - 15 mesh.
[0021] Preferably,
[0022] the outer shell layer is phenolic resin or epoxy resin; preferably, a tracer is mixed in the outer shell layer, and more preferably, the content of the tracer in the outer shell layer is 30 wt% to 50 wt%, preferably 35 wt% to 40 wt%.
[0023] Preferably,
[0024] the tracer is at least one of lanthanum chloride, cerium chloride, holmium chloride, and neodymium chloride.
[0025] Preferably,
[0026] the density of the high-density metal particles is 5 - 12 g / cm 3 , preferably 7 - 10 g / cm 3 ; preferably, the high-density metal particles are at least one of iron, copper, and lead.
[0027] Preferably,
[0028] the elastic modulus of the elastic material coating is not greater than 1 GPa; and / or,
[0029] the melting temperature of the elastic material coating is above 180 °C; and / or,
[0030] Preferably, the elastic material coating is at least one of nitrile rubber, fluororubber, silicone rubber, and polyurethane elastomer.
[0031] The second object of the present invention is to provide a preparation method of a composite material for crack monitoring.
[0032] The preparation method of the composite material according to the present invention includes:
[0033] Spray-drying and coating an elastic material coating on the surface of the high-density metal particles for the first time, and after obtaining composite particles by first curing; then spray-drying and continuously coating an outer shell layer on the surface of the composite particles for the second time, and obtaining the composite material by second curing.
[0034] Preferably,
[0035] the temperature of the first spray-drying is 180 - 200 °C, and / or, during the first spray-drying process, the flow rate ratio of the high-density metal particles to the elastic material coating is (5 - 7):1; and / or,
[0036] the first curing temperature is 20 - 50 °C; and / or,
[0037] The temperature of the second spray drying is 150 - 170 °C, and / or during the second spray drying process, the flow rate ratio of the composite particles to the outer shell layer is (4 - 5):1; and / or
[0038] The temperature of the second curing is 20 - 50 °C.
[0039] The third object of the present invention is to provide a method for using the composite material described above to monitor the lost circulation fractures of drilling fluid.
[0040] The method for using the composite material described in the present invention to monitor the lost circulation fractures of drilling fluid includes:
[0041] During the drilling process, add the composite material along with the drilling fluid. After the drilling is completed, use an acoustic logging instrument to measure the acoustic response of the monitored section. Compared with the typical acoustic characteristic chart of the composite material, the section with abnormal acoustic response is the lost circulation fracture section, and the depth of the lost circulation fracture is determined by the ratio of the acoustic amplitude intensity of the characteristic frequency to the intensity of the typical chart.
[0042] Preferably,
[0043] The addition amount of the composite material is that the volume ratio of the composite material to the drilling fluid is 1:(20 - 50).
[0044] Specifically, the following scheme can be adopted:
[0045] During the drilling process, the composite material circulates with the drilling fluid. When lost circulation occurs, the composite material enters the lost circulation fractures or fracture-cavities along with the drilling fluid. After the drilling is completed, use an acoustic logging tool to measure the lost circulation position and depth by emitting acoustic waves and receiving the frequency and acoustic intensity characteristics of the reflected acoustic waves in a specific frequency band.
[0046] The present invention utilizes the characteristic acoustic properties of the three-layer composite material, and can realize the safe and efficient measurement of the lost circulation position and lost circulation depth through an acoustic logging instrument. Description of the Drawings
[0047] Figure 1 It is a schematic structural diagram of the composite material of the present invention;
[0048] Figure 2 It is a finished product photo of the composite material of the present invention;
[0049] Figure 3 It is a flow chart of the method for using the composite material of the present invention to monitor the lost circulation fractures of drilling fluid;
[0050] Figure 4 It is a typical acoustic characteristic chart of the composite material in Example 1;
[0051] Figure 5 It is a schematic diagram of the formation with lost circulation to be measured;
[0052] Figure 6 Acoustic test results for Example 1;
[0053] Among them, 1 - high - density metal particles, 2 - elastic material coating, 3 - outer shell layer. Specific implementation mode
[0054] The present invention will be specifically described below in conjunction with specific drawings and embodiments. It is necessary to point out here that the following embodiments are only for further illustration of the present invention and cannot be construed as limiting the protection scope of the present invention. Some non - essential improvements and adjustments made by those skilled in the art based on the content of the present invention still fall within the protection scope of the present invention.
[0055] Example 1
[0056] (1) Using an atomizer, spray - dry iron particles with a flow rate of 5 L / min and polyurethane elastomer with a flow rate of 1 L / min at 185 °C, and cure at 25 °C and 100 KPa to coat the polyurethane elastomer on the surface of the iron particles to obtain composite particles;
[0057] (2) Using an atomizer, at 160 °C, spray - dry the composite particles obtained in step (1) at a flow rate of 4 L / min and a mixture of epoxy resin and lanthanum chloride (the content of lanthanum chloride is 35 wt%) at a flow rate of 1 L / min, and cool and cure at 30 °C and 100 KPa to coat the hard shell of the mixture of epoxy resin and lanthanum chloride on the surface of the composite particles to obtain the required composite material.
[0058] The mesh number of the composite material prepared by the above - mentioned preparation method is 10 - 12 meshes, the ratio of the radius of the iron particles to the thickness of the polyurethane elastomer coating is 1:2.5, and the thickness of the outer shell layer of the mixture of epoxy resin and lanthanum chloride is 80 - 90 microns.
[0059] Among them,
[0060] The polyurethane elastomer is a thermoplastic polyurethane produced by Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd., with an elastic modulus of 0.1 GPa and a melting temperature of 180 °C;
[0061] The epoxy resin is a four - functional high - temperature - resistant epoxy resin of model AG80 produced by Kailvwei Chemical Co., Ltd.;
[0062] The lanthanum chloride is produced by Ganzhou Guangli High - tech Materials Co., Ltd.;
[0063] The iron particles are 30 - 35 - mesh iron ball particles produced by Jinan Groot Co., Ltd., with a density of 7.8 g / cm 3 .
[0064] Example 2
[0065] (1) using an atomizer to spray-dry iron particles at a flow rate of 5 L / min and silicone rubber at a flow rate of 1 L / min at 185° C., curing at 25° C. and 100 KPa, and coating the silicone rubber on the surface of the iron particles to obtain composite particles;
[0066] (2) Using an atomizer at 160° C., the composite particles obtained in step (1) are mixed with a mixture of epoxy resin and lanthanum chloride (the content of lanthanum chloride is 40 wt%) at a flow rate of 1 L / min at a flow rate of 4 L / min, and cooled and solidified at 30° C. and 100 KPa, and the mixture of epoxy resin and lanthanum chloride is hard-shell coated on the surface of the composite particles to obtain the desired composite material.
[0067] The mesh number of the composite material prepared by the preparation method is 12-15 meshes, the ratio of the radius of the iron particles to the thickness of the silicone rubber coating is 1:3, and the thickness of the outer shell layer of the mixture of epoxy resin and lanthanum chloride is 70-80 microns.
[0068] in,
[0069] The silicone rubber is a high temperature resistant silicone rubber of model TN-29X0H / Y produced by Tianan Silicone Technology Co., Ltd., with an elastic modulus of about 0.9 GPa, a Poisson's ratio of about 0.48, and a melting temperature of 180°C;
[0070] The epoxy resin is AG80 tetrafunctional high temperature resistant epoxy resin produced by Kailuwei Chemical Co., Ltd.
[0071] Lanthanum chloride was produced by Ganzhou Guangli High-tech Materials Co., Ltd.;
[0072] The iron particles are 30-35 mesh iron balls produced by Jinan Grut Co., Ltd., with a density of 7.8g / cm 3 .
[0073] Example 3
[0074] (1) using an atomizer to spray-dry lead particles at a flow rate of 7 L / min and nitrile rubber at a flow rate of 1 L / min at 190° C., curing at 25° C. and 100 KPa, and coating the nitrile rubber on the surface of the lead particles to obtain composite particles;
[0075] (2) Using an atomizer at 160° C., the composite particles obtained in step (1) are mixed with a mixture of epoxy resin and cerium chloride (the content of cerium chloride is 35 wt%) at a flow rate of 1 L / min at a flow rate of 4 L / min, and cooled and solidified at 40° C. and 100 KPa, and the mixture of epoxy resin and cerium chloride is hard-shell coated on the surface of the composite particles to obtain the desired composite material.
[0076] The mesh number of the composite material prepared by the above preparation method is 15 - 18 meshes, the ratio of the radius of the lead particles to the thickness of the nitrile rubber coating is 1:2, and the thickness of the outer shell layer of the mixture of epoxy resin and cerium chloride is 50 - 55 microns.
[0077] Among them,
[0078] The nitrile rubber is high-performance powdered nitrile rubber produced by Beiwei Technology, with an elastic modulus of 0.3 GPa and a melting temperature of 180 °C;
[0079] The epoxy resin is the four-functional high-temperature resistant epoxy resin of model AG80 produced by Kailvwei Chemical Co., Ltd.;
[0080] The cerium chloride is produced by Ganzhou Guangli High-tech Materials Co., Ltd.
[0081] The lead particles are 35 - 42 mesh lead ball particles produced by JGYC, with a density of 11.7 g / cm 3 .
[0082] Example 4
[0083] The composite material prepared in Example 1 was used for the test of lost circulation fractures in drilling fluid. The specific process for measuring the lost circulation position and depth is as Figure 3 shown: First, prepare more than 1 ton of composite material particles of 10 - 20 meshes. During the drilling process, the composite material is added according to the volume ratio of the composite material to the drilling fluid of 1:20. After the drilling is completed, use a sonic logging instrument to drag the instrument along the wellbore to measure the acoustic response of the monitoring section. The section with abnormal acoustic response is the lost circulation section, and the lost circulation depth is determined by comparing the characteristic frequency amplitude intensity with the typical acoustic characteristic chart of the composite material.
[0084] Among them, the test method for the typical acoustic characteristic chart of the composite material prepared in Example 1 is: Under ground conditions, at 20 °C and atmospheric pressure, stack the composite material in a columnar container with a length of 1 m and a diameter of 10 cm, and measure the acoustic chart. The chart is measured under the condition of an incident sound pressure of 1 Pa, and the acoustic wave penetration loss L = αr10 -3 , and the sound intensity loss is proportional to the distance. The test results are as Figure 4 shown.
[0085] As Figure 6 shown, during the test of the sonic logging instrument, characteristic acoustic waves are displayed at two positions. The amplitude intensity shows that the maximum amplitude at point A is 1.5 times that of the standard acoustic wave chart, and the maximum amplitude at point B is 3.2 times that of the standard acoustic wave chart. Therefore, it is determined that the ratio of the lost circulation section depth at point A to the lost circulation section depth at point B is approximately 1:2.
Claims
1. A composite material for crack monitoring, characterized in that The composite material includes: High-density metal particles, an elastic material coating coated on the high-density metal particles, and a shell layer coated on the elastic material; The ratio of the radius of the high-density metal particles to the thickness of the elastic material coating is 1:(1-5); The thickness of the shell layer is 50-500 microns.
2. The composite material according to claim 1, wherein: The ratio of the radius of the high-density metal particles to the thickness of the elastic material coating is 1:(2-3); The thickness of the shell layer is 50-100 microns.
3. The composite material according to claim 1, wherein: The composite material is spherical particles. Preferably, the spherical particles are 10 mesh to 20 mesh, preferably 10 mesh to 15 mesh.
4. The composite material according to claim 1, wherein: The shell layer is phenolic resin or epoxy resin; preferably, a tracer is mixed in the shell layer. More preferably, the content of the tracer in the shell layer is 30 wt% to 50 wt%, preferably 35 wt% to 40 wt%.
5. The composite material according to claim 4, wherein: The tracer is at least one of lanthanum chloride, cerium chloride, holmium chloride, and neodymium chloride.
6. The composite material according to claim 1, wherein: The density of the high-density metal particles is 5-12 g / cm 3 , preferably 7-10 g / cm 3 ; preferably, the high-density metal particles are at least one of iron, copper, and lead.
7. The composite material according to claim 1, wherein: The elastic modulus of the elastic material coating is not greater than 1 GPa; and / or, The melting temperature of the elastic material coating is above 180 °C; and / or, Preferably, the elastic material coating is at least one of nitrile rubber, fluororubber, silicone rubber, and polyurethane elastomer.
8. A method for preparing a composite material according to any one of claims 1-7, characterized in that The method includes: Spray-drying and coating an elastic material coating on the surface of high-density metal particles for the first time. After obtaining composite particles by first curing; spray-drying and continuously coating a shell layer on the surface of the composite particles for the second time, and obtaining the composite material by second curing.
9. The preparation method according to claim 8, wherein: The temperature of the first spray-drying is 180-200 °C, and / or, during the first spray-drying process, the flow rate ratio of the high-density metal particles to the elastic material coating is (5-7):1; and / or, The temperature of the first curing is 20-50 °C; and / or, The temperature of the second spray-drying is 150-170 °C, and / or, during the second spray-drying process, the flow rate ratio of the composite particles to the shell layer is (4-5):1; and / or, The temperature of the second curing is 20-50 °C.
10. A method for using the composite material as described in any one of claims 1-7 or the composite material obtained by the preparation method as described in claim 8 or 9 to monitor lost circulation fractures in drilling fluids, characterized in that The method includes: During the drilling process, adding the composite material along with the drilling fluid. After the drilling is completed, use a sonic logging instrument to measure the acoustic response of the monitored section. Compared with the typical acoustic characteristic chart of the composite material, the section with abnormal acoustic response is the lost fracture section, and the depth of the lost fracture is determined by the ratio of the characteristic frequency amplitude intensity to the intensity of the typical chart.
11. The method according to claim 10, wherein: The addition amount of the composite material is that the volume ratio of the composite material to the drilling fluid is 1:(20-50).
Citation Information
Patent Citations
Drilling fluid leak position detection system and method
CN109424356A
Method for actively detecting lost circulation by using radioactive indicators
CN110847897A
Ground stress azimuth prediction method based on microseism
CN113687411A
Drilling fluid leakage position measuring device and measuring method
CN116066085A
Split type drilling fluid leaks dislocation puts measuring instrument
CN206987806U